PENGEMBANGAN RENCANA PEMBELAJARAN MODEL PEMBELAJARAN STEM UNTUK KELOMPOK B SUB TEMA BENDA-BENDA ALAM - Fauziaturromah, Yuniar; Rahman, Taopik; Mulyana, Edi Hendri (JURNAL PAUD AGAPEDIA, 2021)
The teacher need The Lesson plan for the smooth process of activities in the classroom. The lesson plan must be prepared according to the characteristics of the child. STEM learning is a new breakthrough in learning to face the 21st century and helps develop 4C skills (Communication, Collaborative, Critical Thinking and Creativity). Study is based on the problems that exist in the field related to the STEM learning model learning plan which is still lacking in its application. The STEM learning model learning plan aims to be a reference in the process of implementing learning in the STEM model.Rencana pembelajaran sangat diperlukan oleh guru untuk kelancaran proses kegiatan di kelas. Rencana pembelajaran harus disusun sesuai dengan karakteristik anak. Pembelajaran STEM merupakan terobosan baru dalam pembelajaran untuk menghadapi abad 21 dan membantu mengembangkan keterampilan 4C (Communication, Collaborative,Critical Thingking and Creativity). Latar belakang dalam penelitian ini berdasarkan permasalahan yang ada di lapangan berkaitan dengan rencana pembelajaran model pembelajaran STEM yang masih kurang dalam penerapannya. Rencana pembelajaran model pembelajaran STEM bertujuan untuk menjadi acuan dalam proses pelaksanaan pembelajaran dalam model STEM.